PENINGKATAN NILAI PERUSAHAAN BERBASIS PROFITABILITAS DAN STRUKTUR MODAL - Aprih Santoso; Witjaksono E.H; Emaya Kurniawati (Adbis: Jurnal Administrasi dan Bisnis, 2019)
The main purpose of companies that have gone public is to increase the prosperity of the owner or shareholders through increasing company value. This study aims to analyze the effect of profitability and capital structure on company value with managerial ownership as a moderating variable in LQ 45 companies. The research method used is quantitative with multiple regression data analysis techniques (path analysis). The results of this study are: (1) Profitability (ROA) is proven to have a significant positive effect on company value (PBV). (2) Profitability (ROA) is proven to have a significant positive effect on the company value (PBV). (3) Capital structure (DER) significantly influences company value (PBV) significantly.